Genre diversification: Orthodoxy and innovation in an Indonesian minority religion - Herrmans, Isabell (Indonesia and the Malay World, 2017)
This article explores adaptation to demands of affiliation with a world religion and increasing religious orthodoxy among followers of the indigenous (Hindu) Kaharingan religion in Indonesian Borneo. It compares ritual practices and notions of religious identity in the provinces of Central Kalimantan (where the local religion has been officially recognised as an agama) and East Kalimantan (where it has not). The empirical material is based on ethnographic fieldwork with the Luangan Dayak who live in both provinces. Different strategies of adapting to state and religious politics have emerged in the two provinces. In Central Kalimantan the recognition of the religion has spurred an extensive rationalisation process causing modification of old practices and the introduction of new ones. In East Kalimantan, an equivalent development is evinced through creative innovation and idiosyncratic adaptation of unrecognised religious practices and the popularisation of a ritual genre incorporating the perspective and aesthetics of ethnic ‘others’. The article concludes that genre diversification allows the Luangan to respond to the challenges of religious politics and social change while maintaining local tradition and practices catering to local concerns. It also argues that genre diversification expresses a constitutive ontological pluralism and propensity for perspectival shifts.
Created from Fastlane, Scopus look-up
Keywords: Agency; Dayak; Kaharingan; Kalimantan; religion; ritual